Enhancing Risk Management Strategies in the Financial Sector - Muhammad Wildanul Atqiya (Arthatama: Journal of Business Management and Accounting, 2024)
Risk management is a critical component in ensuring the stability and sustainability of the financial sector. With the rapid digital transformation and increasing global economic uncertainties, financial institutions face heightened risks related to cybersecurity, regulatory compliance, and economic fluctuations. This study examines contemporary risk management challenges, explores innovative mitigation strategies, and highlights emerging opportunities such as Artificial Intelligence (AI), big data analytics, and sustainability-driven financial practices. A mixed-methods approach is employed, integrating qualitative insights from industry professionals with quantitative analysis of risk trends. The findings underscore the necessity for adaptive risk management frameworks that leverage technological advancements while aligning with regulatory and environmental considerations. This study contributes to the discourse on financial risk management by offering strategic recommendations for enhancing resilience in an increasingly volatile financial landscape.